Dynamic changes and transcriptome analyses reveal the microfilament skeleton response to water stress in thalli of Neopyropia yezoensis inhabiting the intertidal zone - Jiqiang Yin; Ying Sun; Xinping Miao; Jiaxin Qu; Kunjie Zhang; Xue qing Han; Yichi Li; Jiahui Sun; Fanna Kong (Plant Stress)
The microfilament (MF) cytoskeleton, present in all eukaryotic cells, is not only essential for fundamental cellular processes but also is important in sensing and transducing external signals in response to various developmental cues and abiotic stresses. Neopyropia yezoensis, a species of seaweed belonging to the Rhodophyta, is an important macroalga that thrives in the intertidal zone. However, it remains uncertain whether the MF cytoskeleton of seaweed contributes to adaption to desiccation and rehydration. In this study, we present for the first time the evidence regarding the role of MFs in the desiccation tolerance of N. yezoensis. The organization and arrangement of MFs were significantly influenced by variations in the water content within thallus cells. Desiccation of the thallus induced changes of many actin and actin binding proteins (ABPs) at transcriptional, translational and post-translational phosphorylation levels. Notably, nine phosphosites from four proteins (actin, formin, septin, and fascin) showed changes in phosphorylation conditions. This indicate that phosphorylation modification was involved in MFs response to desiccation and rehydration stress. Transcriptome analysis revealed that Latrunculin A, an MF polymerization inhibitor, significantly suppressed the expression of actin and ABPs genes. Further analysis indicated that MF participates in the responses to desiccation in N. yezoensis by regulating plastid function, ROS levels, phosphorylation modification of proteins, Ca2+ signals and vesicle transport processes. Additionally, two MYB transcriptional factors were identified as being induced by regulating the MF cytoskeleton assembly. Finally, we developed a hypothesis concerning the regulation of the microfilament skeleton as a fundamental response to water loss in thalli of N. yezoensis. Our findings will enhance our understanding the adaption mechanisms of N. yezoensis to water stress and broaden our knowledge regarding the response of MF cytoskeleton to water stress. Furthermore, this research will provide valuable insights into the species distribution of intertidal zones.